Expatriate adjustment and organisational citizenship behaviour: a study in an institute of higher education - Smadi Mehtap, Salime (My University, 2001)
Bu çalışmanın amacı yurtdışına çalışmaya giden yabancı öğretim elemanların uyum sürecini ve ayni zamanda uyum ile işyerinde gösterdikleri Örğütsel Vatandaşlık Davranışı (ÖVD) arasındaki ilişkiyi incelemektir.İş tatmininin bir ara değişken olarak uyum ve vatandaşlık ilişkisinde etkili olup olmadığına da bakılmıştır. Bu güne dek yabancı çalışanların uyumu ile ilgili olarak yapılan çalışmalarda daha çok yöneticiler ele alınmıştır. Bu araştırmada ise yabancı öğretim görevlileri incelenmiştir. Kıbrıs'da, ögretim dili

olan bir üniversitede farklı akademik pozisyonlarda, 27 farklı bölümde ve değişik etnik kökenden oluşan 162 öğretim elemanı araştırmaya katılmıştır. Ölçme aracı olarak, uyum ve ÖVD 'lık alanında daha önce güvenirliği kanıtlanmış anketler kullanılmıştır. Şirketleri tarafından yurtdışına gönderilen yabancı yöneticilerin aksine,yabancı öğretim elemanların yurtdışına çalışmaya gitmelerinin 3 temel sebebi; üniversitenin onlara sunduğu cazip imkanlar, üniversite de daha önce çalışan bir arkadaşlarının tavsiyesi ve memleketin ılık iklimi. Toplanılan data'yı incelemek ve 23 tane hipotezi test etmek için bağımsız t-testi, tek yönlü ANOVA, korelasyon ve çoklu regresyon analizi uygulandı.Çıkan sonuçlara göre örgütte çalışılan toplam sürenin, sosyal destekden duyulan tatminin ve iş tatmininin uyumu manidar bir şekilde açıkladığı bulundu. Yanında eşlerini ve/ veya çoçuklarını getiren yabancı öğretim elemanları ve getirmeyenler arasında manidar bir farklılık bulunmadı.Bu memleket hakkında topladıkları ön bilgilerin uyum üzerinde bir etkisi olmadığı görüldü. Öğretim görevlilerin etnik kökeni ile uyumu ve gösterdiği ÖVD'ı arasındaki korelasyon manidar çıkmadı.Öğretim görevlilerinin iş tatmini ve uyum seviyesi ÖVD'ı manidar bir şekilde açıkladığı ğörüldü. Uyum ve ÖVD'ı arasındaki ilişkide iş tatmininin kısmen etkili olduğu görüldü. Son olarak, çalışmanın katkılar, sınırlılıkları ve öneriler örgüt,araştırmacılar ve akademisyenler açışından tartışıldı. ABSTRACT The purpose of this research is to explore the adjustment process for expatriate lecturers and to see if their adjustment is associated with Organisational Citizenship Behaviour that they display within the workplace. The mediating affect of satisfaction with the job on the relationship between expatriate adjustment and Organisational Citizenship Behaviour will also be tested for. To date, scholars have primarily concentrated on the expatriate manager in their attempts to study the phenomenon of expatriate adjustment. This research looked at the adjustment process of a different type of expatriate, namely the expatriate lecturer. 162 lecturers of varying ethnic backgrounds and academic positions and who teach in 27 different departments in a university in North Cyprus, where the medium of instruction is English participated in the study. Lecturers completed questionnaires consisting of reliable instruments within the fields of adjustment and Organisational Citizenship Behaviour. Unlike the expatriate manager who is sent on a foreign assignment by his company, the three main reasons why expatriate lecturers chose to go abroad to teach were the attractive pay and benefits package offered by the university, a friend already working there recommended it and the mild climate of the country. Independent t-tests, ANOVA, Correlation analysis and Multiple Regression analysis was used to analyze the data and test a total of 23 hypotheses. Results indicated that significant predictors of expatriate adjustment were time in the host organization, satisfaction with social support and satisfaction with the job. No significant difference was found between those expatriates who were accompanied by spouse and / or children and those who were not. As the expatriate lecturer does not undergo training before going abroad, the amount of self initiated pre-departure information they tried to collect about the host culture did not have an effect on their adjustment. The ethnic background of the expatriate lecturer was also not linked to their adjustment and displays of Organisational Citizenship Behaviour. Adjustment was significantly correlated with Organisational Citizenship Behaviour. Significant predictors of an expatriate's level of Organisational Citizenship Behaviour were satisfaction with the job and their level of adjustment. Finally an expatriate's degree of satisfaction with the job had a partially mediating effect on the relationship between adjustment and Organisational Citizenship Behaviour. Contributions, limitations and implications for the organization, practitioners and academicians are discussed.
Keywords: Örgütsel Davranış